Study on Combined Energy Absorption Support for Rockburst Disaster Control in Tunnelling - Liang Kuang; Gang Wang; Wenge Qiu; Lun Gong; Zhiqiang Feng; Tianhui Ma (Shock and Vibration)
In order to better realize the rockburst disaster control mechanism and approach, the rockburst response of concrete blocks with different energy absorption levels under different energy storage conditions was observed and analyzed by loading tests. The occurrence and control mechanism of rockburst were explored from the perspective of energy aggregation and energy dissipation. On this basis, a combined energy absorption support system of concrete-filled steel tube frames and hollow steel pipes for rockburst disaster control was designed, and the effectiveness of the system was verified by numerical simulation and field tests. The results of loading tests show that the failure mode of the specimens changes from static failure to dynamic burst under energy storage loading. The occurrence of rockburst is inevitable when the energy supply is sufficient, but the disaster can be reduced or eliminated by strengthening constraints and improving energy-absorbing capacity to transform rockburst into large deformation. The combined structure consists of the hollow steel pipes being energy-absorbing part and the concrete-filled steel tube frames being strong confinement part was proposed to control rockburst disaster in tunnel support. The numerical analysis on the dynamic response of the support under strong rockburst impact shows that the hollow steel pipes effectively reduced the impact force on the concrete-filled tube frames, and accordingly, the deformation of the entire support system decreased. Given the condition that the hollow steel pipes be able to absorb all the impact energy during deformation, the smaller the strength of the hollow steel pipe is, the smaller the impact force and the displacement is. The combined energy absorption support provides an effective solution for rockburst disaster management in tunnels with strict clearance requirements.